MR of postoperative syringomyelia. - Barkovich, A J; Sherman, J L; Citrin, C M; Wippold, F J (American Journal of Neuroradiology, 1987)
Twenty-seven MR scans of 20 patients surgically treated for syringomyelia were reviewed. Thirteen patients had syringomyelia associated with the Chiari I malformation, four cases were posttraumatic, and three were idiopathic. The operations performed included syringosubarachnoid and syringoperitoneal shunts, myelotomies, and foramen magnum decompressions. Three of the foramen magnum decompressions had associated posterior fossa duroplasties, two had fourth-ventricle-to-subarachnoid shunts, and two had plugging at the obex. On 20 scans of patients in whom the syrinx cavity had been shunted, the shunt catheter was seen in 15 (75%). When adequately treated by shunting, syringes are completely collapsed and show no flow void. Nine patients were treated by foramen magnum decompression; all were well seen by MR. Three of these patients had a poor clinical result; these were the only patients in whom CSF was not seen between the foramen magnum and the neural structures of the posterior fossa on any images. The proposed mechanisms of syrinx formation and extension are discussed and related to the surgical procedures used to treat syringomyelia.